2014
DOI: 10.1007/s12028-014-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Argon Administration Provides Robust Protection Against Cardiac Arrest-Induced Neurological Damage

Abstract: Our study demonstrates that a 1-h application of argon provided a significant reduction in histopathological damage, associated with a marked improvement in functional neurologic recovery even when treatment was delayed for 3 h. This is highly significant with regard to clinical situations, where argon treatment cannot be provided timely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 27 publications
0
39
1
2
Order By: Relevance
“…In rodents, Brücken et al showed that the administration of argon 1 h after cardiac arrest improved functional neurological recovery after experimental cardiac arrest [6,19]. The same result was observed when argon was administered 3 h after cardiac arrest [20]. Pigs receiving post-resuscitation treatment with argon also had complete neurological recovery [7].…”
Section: Discussionmentioning
confidence: 86%
“…In rodents, Brücken et al showed that the administration of argon 1 h after cardiac arrest improved functional neurological recovery after experimental cardiac arrest [6,19]. The same result was observed when argon was administered 3 h after cardiac arrest [20]. Pigs receiving post-resuscitation treatment with argon also had complete neurological recovery [7].…”
Section: Discussionmentioning
confidence: 86%
“…The noble gases Ar and Xe have also previously been investigated as a reconditioning strategy in IRI kidney transplant models showing beneficial effects on graft function 1213. But since the protective effect of Ar seems to be dose-dependent,14 a higher and longer exposure to Ar to protect against pulmonary ischemia reperfusion injury seemed justified. A prolonged exposure to Ar can be achieved by introducing the gas earlier in the process of organ donation 15.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological damage in the cortex and hippocampal region was reduced, resulting in an improved functional neurological outcome up to 3 days after injury. This improvement was even shown by applying argon 1 delayed hour after CPR GABAA receptor gamma-aminobutyric acid A receptor; LPS lipopolysaccharide; ERK1/2 extracellular signal-regulated kinases 1/2; MEK1/2 = MAPKK mitogen-activated protein kinase; mTOR mammalian target of rapamycin; Nrf2 nuclear factor (erythroid-derived 2)-like 3; TLR Toll-like receptor; NF-κB nuclear factor "kappa-light-chainenhancer" of activated B cells [110,111]. Following these promising results, argon was added to mild hypothermia in the same model.…”
Section: Neuroprotection By Argonmentioning
confidence: 99%